The Relevance of Islamic Teaching in Madrasah Diniyah within Semi-Urban Communities - Adzhar, Moh Hanif; Fitroroh, Umil Mu’alimatun Muzaroh; Arsyadana, Addin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
Society today stands at a crossroads between tradition and modernity. People are vulnerable to shifts in values due to massive developments, such as deviant behavior, the erosion of traditions, and a lack of religious understanding. Therefore, there is a need for spiritual education that integrates spirituality and morality, as in Madrasah Diniyah. The purpose of this study is to examine the relevance of Islamic teaching at Madrasah Diniyah in response to shifting values in semi-urban areas. This study uses a qualitative, case-study approach. The results show that Madrasah Diniyah has succeeded in instilling good character values in students through consistent teaching of faith, morals, and worship practices, thereby increasing their spiritual and moral sensitivity. Student participation in local traditions strengthens their understanding and appreciation of culture with noble values rooted in society. Affordability, flexibility in learning time, and regional content in the curriculum are responses to community needs. The findings show that Islamic teaching in Madrasah Diniyah is relevant to the conditions of semi-urban communities, thereby helping build children’s spirituality and morals, increasing understanding of community traditions, and providing easy access to needs. This study is limited to narrative analysis, a specific regional context, and a limited number of informants. Further studies are recommended to analyze the broader community’s perception of Islamic teaching at Madrasah Diniyah through a quantitative approach.